Depressive symptoms of the elderly people and caregiver’s burden in home care - Girardi Paskulin, Lisiane Manganelli; Kottwitz Bierhals, Carla Cristiane Becker; Oliveira dos Santos, Naiana; Baltar Day, Carolina; de Oliveira Machado, Diani; Pinheiro de Morais, Eliane; Rodrigues Gonçalves, Marcelo; Peixoto Cordova, Fernanda; Ferreira Grillo, Maria de Fátima (Investigación y Educación en Enfermería, 2017)
Objective. To characterize the elderly population and their caregivers and to verify the association of depressive symptoms of the elderly and the caregiver’s burden with the variables of interest. Methods. A cross-sectional study with 80 elderly people and 78 caregivers in a Primary Health Service in southern Brazil. Retrospective collection conducted in a structured database based on the multidimensional evaluation tool applied to home care for the elderly participants and their caregivers. Results. Most elderly participants were women (71.3%), with an average age of 82.1 years and 52.6% reported sadness or discouragement. Systemic arterial hypertension was the most frequent morbidity (68.8%). Most caregivers were women (85.7%), daughters of the elderly person (53.2%), mean age 57.8 years and 38.7% reported feeling the burden. The presence of depressive symptoms in the elderly was associated with Parkinson’s disease (p=0.016) and to have a male caregiver (p=0.006). Caregiver’s burden was associated with daily life activities such as bathing (p=0.021). Conclusion. There was evidence of differences in caregiver’s gender in the presence of depressive symptoms and differences in the assistance in daily life activities for the caregiver’s burden. How to cite this article: Paskulin LMG, Bierhals CCBK, Santos NO, Day CB, Machado DO, Morais EP, et al. Depressive symptoms of elderly people and caregiver’s burden in Home Care. Invest. Educ. Enferm. 2017; 35(2):210-220.